RENEB biodosimetry intercomparison analyzing translocations by FISH. (2nd January 2017) - Barquinero, Joan Francesc; Beinke, Christina; Borràs, Mireia; Buraczewska, Iwona; Darroudi, Firouz; Gregoire, Eric; Hristova, Rositsa; Kulka, Ulrike; Lindholm, Carita; Moreno, Mercedes; Moquet, Jayne; Oestreicher, Ursula; et al.
Abstract: Purpose: In the framework of RENEB, several biodosimetry exercises were conducted analyzing different endpoints. Among them, the analysis of translocations is considered the most useful method for retrospective biodosimetry due to the relative stability of their frequency with post irradiation time. The aim of this study was to harmonize the accuracy of translocation-based biodosimetry within the RENEB consortium. Materials and methods: An initial telescoring exercise analyzing FISH metaphase images was done to harmonize chromosome aberration descriptions. Then two blind intercomparison exercises (IE) were performed, by sending irradiated blood samples to each partner. Samples were cultured and stained by each partner using their standard protocol and translocation frequency was used to produce dose estimates. Results: The coefficient of variation in the 1st IE (CV = 0.34) was higher than in the 2nd IE (CV = 0.16 and 0.23 in the two samples analyzed), for the genomic frequency of total translocations. Z-score analysis revealed that eight out of 10 and 17 out of 20 dose estimates were satisfactory in the 1st and 2nd IE, respectively. Conclusions: The results obtained indicate that, despite the problems identified in few partners, which can be corrected, the RENEB consortium is able to carry out retrospective biodosimetry analyzing the frequency of translocations by FISH.